TOURISM AND INTERNATIONAL RELATIONS. FACTORS THAT INFLUENCE TO THE TOURISM INDUSTRY PROMOTION. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Tourism and international relations are interdependent sectors that mutually shape each other. As global mobility expands, tourism becomes both a product and a driver of diplomatic cooperation, economic integration, cultural exchange, and soft power. This article analyzes how political stability, international cooperation, global branding, visa policies, transportation networks, and digital diplomacy influence the promotion of the tourism industry. The study is based on an analytical review of academic literature, global tourism reports, and comparative evaluation of successful international tourism strategies. Results show that countries with strong diplomatic relations, well-established international partnerships, and proactive image-building policies experience higher tourism competitiveness. The article also provides policy recommendations aimed at strengthening tourism promotion through improved bilateral relations, sustainable tourism strategies, and digital communication.